Odpowiedź :
Odpowiedź:
a)7⁶*7¹²=7⁶⁺¹²=7¹⁸ 5*5⁶*5⁰*5⁴=5¹⁺⁶⁺⁰⁺⁴=5¹¹
b)[tex](\frac{2}{3})^2*(\frac{2}{3} )^2*(\frac{2}{3} )^0 =(\frac{2}{3} )^{5+2+0}}=(\frac{2}{3} )^7[/tex] (2a)³*(2a)⁷=(2a)³⁺⁷=(2a)¹⁰
c)(-12)⁴*(-12)⁸*(-12)⁵=(-12)⁴⁺⁸⁺⁵=(-12)¹⁷ [tex](1\frac{1}{4} )^5*(1\frac{1}{4})^7*(1\frac{1}{4} )^2=(1\frac{1}{4} )^{5+7+2}}=(1\frac{1}{4} )^{14}}[/tex]
Szczegółowe wyjaśnienie:
a) [tex]7^{6}[/tex] · [tex]7^{12}[/tex] = [tex]7^{18}[/tex]
5 · [tex]5^{6}[/tex] · [tex]5^{0}[/tex] · [tex]5^{4}[/tex] = [tex]5^{11}[/tex]
b) ([tex]\frac{2}{3}[/tex][tex])^{6[/tex] · ([tex]\frac{2}{3}[/tex][tex])^{2}[/tex] · ([tex]\frac{2}{3}[/tex][tex])^{0}[/tex] = ([tex]\frac{2}{3}[/tex][tex])^{7}[/tex]
(2a[tex])^{3}[/tex] · (2a[tex])^{7}[/tex] = (2a[tex])^{10}[/tex]
c) (-12[tex])^{4}[/tex] · (-12[tex])^{8}[/tex] · (-12[tex])^{5}[/tex] = (-12[tex])^{17}[/tex]
(1[tex]\frac{1}{4}[/tex][tex])^{5}[/tex] · (1[tex]\frac{1}{4}[/tex][tex])^{7}[/tex] · (1[tex]\frac{1}{4}[/tex][tex])^{2}[/tex] = (1[tex]\frac{1}{4}[/tex][tex])^{14}[/tex]